2018
DOI: 10.3233/jad-180179
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic Proteome of Non-Demented Individuals with Alzheimer’s Disease Neuropathology

Abstract: Some individuals, here referred to as Non-Demented with Alzheimer’s Neuropathology (NDAN), retain their cognitive function despite the presence of amyloid plaques and tau tangles typical of symptomatic Alzheimer’s disease (AD). In NDAN, unlike AD, toxic amyloid-β oligomers do not localize to the postsynaptic densities (PSDs). Synaptic resistance to amyloid-β in NDAN may thus enable these individuals to remain cognitively intact despite the AD-like pathology. The mechanism(s) responsible for this resistance rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 164 publications
(194 reference statements)
2
35
0
Order By: Relevance
“…Our results demonstrated no significant differences in PSD95 between the Aβ+ and Aβ− groups of old monkey brains. These data are consistent with human studies showing that the brains of cognitively healthy old humans and nondemented individuals with Alzheimer's disease neuropathology had Aβ deposits but did not show synapse loss (Selkoe & Hardy, ; Zolochevska et al, ). The lack of change in the abundance of Tau and p‐Tau in monkeys may partially explain the lack of synapse and neuronal loss and AD development in aged monkeys (Heuer et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results demonstrated no significant differences in PSD95 between the Aβ+ and Aβ− groups of old monkey brains. These data are consistent with human studies showing that the brains of cognitively healthy old humans and nondemented individuals with Alzheimer's disease neuropathology had Aβ deposits but did not show synapse loss (Selkoe & Hardy, ; Zolochevska et al, ). The lack of change in the abundance of Tau and p‐Tau in monkeys may partially explain the lack of synapse and neuronal loss and AD development in aged monkeys (Heuer et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we used rhesus monkeys, which develop cerebral Aβ deposits spontaneously with advancing age in a process thought to be similar to that which occurs in humans. Aβ deposits sometimes spontaneously occurred in the brains of cognitively healthy old humans and nondemented individuals with Alzheimer's disease neuropathology (Rodrigue et al, ; Zolochevska, Bjorklund, Woltjer, Wiktorowicz, & Taglialatela, ). We previously quantified the levels of insoluble Aβ42 in the brain of frontal cortex and temporal cortex of old monkeys (Zhao et al, ) and found that it was comparable to the levels of insoluble Aβ42 in healthy old human brains with Aβ deposits, but lower than the levels of insoluble Aβ42 in AD patient brains (Steinerman et al, ; Wang, Dickson, Trojanowski, & Lee, ).…”
Section: Discussionmentioning
confidence: 99%
“…This may well be a misleading argument and one which reflects an inherent resistance in these individuals to the initiating actions of Aβ in the amyloid cascade of disease progression or may suggest the involvement of an APP‐related species distinct from Aβ. An examination of the postsynaptic proteome of such NDAN individuals provides some veracity to this hypothesis identifying a unique proteomic signature for the NDAN postsynaptic densities (Zolochevska, Bjorklund, Woltjer, Wiktorowicz, & Taglialatela, ). Enhanced neurogenesis may also play a part, and these dementia‐resistant subjects also show an increased number of neural stem cells and new neurons in the hippocampal dentate gyrus as well as a unique expression of neurogenesis‐regulating miRNAs (Briley et al, ).…”
Section: Pathways To Amyloid Its Clearance and Neuronal Toxicitymentioning
confidence: 99%
“…Aβ oligomer preparation is a technique, used routinely by our laboratory [19]. Briefly, lyophilized Aβ1-42 aliquots (Department of Biophysics and Biochemistry, Yale University, New Haven, CT) were dissolved in 200 μl of 1,1,1,3,3,3-hexafluoro-2-propanol and then added to 700 μl of distilled deionized H 2 O in microcentrifuge tubes.…”
Section: Aβ Oligomer Preparationmentioning
confidence: 99%
“…A different, possibly more efficient approach in search of novel therapies can be taken stemming from the observation that some individuals, here referred to as NDAN, non-demented with Alzheimer's neuropathology, are able to retain cognitive function despite the presence of AD-like pathology (reviewed by [15]). Specifically, NDAN individuals show little or no synapse loss [16], along with preserved neurogenesis potentially regulated by microRNAs [17], as well as PSDs that present with a unique proteomic signature [18] and are resistant to Aβ oligomer binding [19], thus protecting synapses from Aβ oligomer-driven dysfunction and likely contributing to maintenance of cognitive ability despite the presence of AD neuropathology. These observations suggest that NDAN individuals are resilient to the cognitive decline that normally ensues as a consequence of accumulation of AD-like neuropathology.…”
Section: Introductionmentioning
confidence: 99%